Chondrocranium and visceral skeleton of Atelopus tricolor and Atelophryniscus chrysophorus tadpoles (Anura, Bufonidae) - Lavilla, Esteban Orlando (2001)
Atelopus tricolor and Atelophryniscus chrysophorus have gastromyzophorous tadpoles. Aside from specific differences, the larval chondrocrania and visceral skeletons show several shared character states, including an almost quadrangular, open chondrocranium, cornua trabeculae with expanded tips, cartilago suprarostralis as a single element, a posteriorly projected arcus subocularis quadrati, a closed muscular tunnel, and a simplified branchial basket, with only three pairs of ceratobranchiales. They are compared with diverse character states of suctorial larvae considering them as causally related to the stream life adaptations.